2008
DOI: 10.1136/jech.2007.064188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of allostatic load on the social gradient in ischaemic heart disease and periodontal disease: evidence from the Third National Health and Nutrition Examination Survey

Abstract: Indicators of allostatic load were associated with ischaemic heart disease and periodontal disease and had a mediating effect partly explaining the social gradients in both diseases. The results suggest a possible common stress pathway linking socioeconomic position to both conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
110
2
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 35 publications
6
110
2
4
Order By: Relevance
“…11 Prior research has shown higher AL to be associated with mortality, cardiovascular disease, and decreased physical and cognitive functioning. 8,9,[15][16][17][18][19] The formulation of AL by McEwen and Seeman 13 and Seeman et al 10 included primary mediators and secondary markers involved in physiological stress responses. Primary mediators are circulating hormonal agents that mediate the body's response to stressors through their effects on tissues and organs (e.g., cortisol, epinephrine, C-reactive protein [CRP] and dehydroepiandrosterone-sulfate [DHEA-S]).…”
Section: Introductionmentioning
confidence: 99%
“…11 Prior research has shown higher AL to be associated with mortality, cardiovascular disease, and decreased physical and cognitive functioning. 8,9,[15][16][17][18][19] The formulation of AL by McEwen and Seeman 13 and Seeman et al 10 included primary mediators and secondary markers involved in physiological stress responses. Primary mediators are circulating hormonal agents that mediate the body's response to stressors through their effects on tissues and organs (e.g., cortisol, epinephrine, C-reactive protein [CRP] and dehydroepiandrosterone-sulfate [DHEA-S]).…”
Section: Introductionmentioning
confidence: 99%
“…They admit, however, that evidence of causality remains weak. No explanations are offered to account for why these diseases, traditionally conceptualized both as distinguishable from one another and as belonging to different taxonomies, not only seem to cluster into recognizable patterns but also to be characterized by parallel social gradients [12][13][14]. Reference is made, however, to a ''common denominator,'' namely inflammation.…”
Section: Introductionmentioning
confidence: 94%
“…The term "allostatic load" was coined by McEwen and refers to physiological costs of chronic exposure to neural or neuroendocrine stress response [16,17]. The allostatic state is unable to guarantee the good management of the physiological systems and consequently the health status and the individual's well-being, and this phenomena often leads to the development of psychological and psychiatric symptoms [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Among the several nonpharmacological strategies today available to reduce and/or to treat the symptomatic effects of the stress and to improve the allostatic response [33,34], of particular interest appears the use of electrical and electromagnetic stimulation [35], also exploiting the "classical" acupuncture points [36,37].…”
Section: Introductionmentioning
confidence: 99%